Industrial first aid equipment: a historical analysis (1840-1914) - Porro, Alessandro; Franchini, Antonia Francesca; Lorusso, Lorenzo; Falconi, Bruno (La Medicina del Lavoro, 2015)
Even if references to the tools required to intervene after an accident can be found in the works of Bernardino Ramazzini (1633-1714) or Johann Peter Frank (1745-1821), it was only with the development of industrial manufacturing that the need to study means to prevent and intervene in cases of accident became evident. In October 1894 the III Congrés International des Accidents du Travail et des Assurances Sociales was held in Milan. The following year, the Milanese trade union movement acknowledged the necessity to address the problem of industrial accidents. In 1896 the Association for Medical Assistance in Industrial Accidents was founded in Milan. A specific medical institute was set up, appropriate first aid tools were collected and first aid rooms in the main Milanese factories were inaugurated. Nevertheless, few data seem to be available regarding the manufacture and use of this equipment in industry. We analyzed more than fifty catalogs of European industrial products, between 1843 and 1914, to study the evolution of first aid equipment for industrial use. They reflect and attest to the evolution of medicine and surgery, although some models seem to be related to certain industrial categories (railways, electrical appliances), some were similar to ordinary first aid boxes, others were strictly related to surgery; some could only be used by physicians, and others only by workers. Identification, conservation, and reappraisal of these tools is essential for historians of occupational health because these objects were normally not preserved. The catalogues of industrial production are also precious sources, since they are rarely preserved in public libraries and deserve to be used for historical studies.